1983
DOI: 10.1182/blood.v61.2.297.bloodjournal612297
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and morbidity of central nervous system "prophylaxis" in childhood acute lymphoblastic leukemia: eight years' experience with cranial irradiation and intrathecal methotrexate

Abstract: Between 1972 and 1979, 214 children with acute lymphoblastic leukemia and no evidence of central nervous system (CNS) disease prior to CNS prophylaxis were treated with 2400 rad cranial irradiation and concurrent intrathecal methotrexate. Only nine children developed CNS leukemia; five of them in the CNS only and four concurrently in the CNS and another site. Major acute effects of CNS prophylaxis were seizures in seven patients (3%). Sixty-nine children who had a minimum follow-up of 4 yr were evaluable for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…ALL has a propensity to spread to the CNS and thus treatment includes prophylactic CNS therapy. The latter is associated with frequent and well‐documented long‐term cognitive sequelae 1, 24–29. Historically, CNS treatment included whole brain radiation and intrathecal chemotherapy; however, because of the long‐term cognitive sequelae of cranial radiation, current CNS treatments omit radiation for a large majority of children with ALL and use both intrathecal and systemic chemotherapy only.…”
Section: Introductionmentioning
confidence: 99%
“…ALL has a propensity to spread to the CNS and thus treatment includes prophylactic CNS therapy. The latter is associated with frequent and well‐documented long‐term cognitive sequelae 1, 24–29. Historically, CNS treatment included whole brain radiation and intrathecal chemotherapy; however, because of the long‐term cognitive sequelae of cranial radiation, current CNS treatments omit radiation for a large majority of children with ALL and use both intrathecal and systemic chemotherapy only.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cataract in children treated for ALL varies among studies and is generally reported to not significantly impact vision 2,20–24 . In our cohort, new cataract formation was the most frequent abnormality after the conclusion of therapy and was associated with higher occurrence of vision deficits.…”
Section: Discussionmentioning
confidence: 54%
“…The incidence of cataract in children treated for ALL varies among studies and is generally reported to not significantly impact vision. 2,[20][21][22][23][24] In our cohort, new cataract formation was the most frequent abnormality after the conclusion of therapy and was associated with higher occurrence of vision deficits. We observed a cumulative incidence of cataract of 13% at 43 months from diagnosis, and additional cases were registered with longer follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Sekundllre Mallgnome spielen als Therapiefolge der Meningealkarzinose keine Rolien, können jedod nadh Jahren bzw. mntrathekai prophyiaktisdher Be-handlung Bedeutung erlangen (17). So berichtete Fontana (11) uber insgesamt 17 Patienten, die mehrere Jahre nach erfoigreich behandelter ALL vornehmlich Astrozytome Grad III und IV sowie Glioblastome im Alter zwischen 9 und 17 Jahren entwickelten.…”
Section: Course Of Meningeal Tumorousunclassified
“…Nebenwir/cungen von intrathekal MTX allein oder kombiniert mit Strahientherapie sind(8,9,17,29,42,47): Arachnitis: Akuteinsetzen der Symptomatik innerhath von 24-72 Stunden nach intrathekaler MTX-Applikation mit Kopfschmerz, Ubelkeit und Erbrechen. Diese Kompilkation ist bei unseren Patienten nicht dokumentiert (in der Literatur 5-40%, zit.…”
unclassified